Drainage management study of the city of Merauke towards inundation by rainfall - Kusumabrata, Luffi; Andawayanti, Ussy; Suhartanto, Ery (Civil and Environmental Science Journal (CIVENSE), 2020)
One problem that is often faced by the City of Merauke as an urban area is inundation, which disrupts socio-economic activities and damages infrastructure in areas affected by inundation. The aim of this case study is to find ways to deal with inundation that occurs due to rainfall with return periods of 2 years, 5 years, 10 years, and 25 years. The inundation volume for the 2-year return period is zero, for the 5-year return period is 12.58 m3/sec with a height of 23.35 cm, for the 10-year return period is 18.57 m3/sec with a height of 25.63 cm, and for the 25-year return period is 20.22 m3/sec with a height of 27.75 cm. With the Microsoft Excel application, hydrological analysis was performed; spatial analysis using Geographic Information Systems (GIS) resulted in a map of the characteristics of the case study area, and with the Storm Water Management Model (SWMM), hydraulics analysis was performed on existing drainage channels along with simulated management.